PLUSES AND MINUSES FOR INDONESIA IN DECIDING WHETHER TO RATIFY THE MADRID PROTOCOL CONCERNING THE INTERNATIONAL REGISTRATION OF TRADE MARK (Lex Jurnalica, 2019)
AbstractThis research examines the issues related to the ratify the Madrid Protocol concerning the International registration of trade mark. This research will examines how the impact of ratification of Madrid System would not only for Indonesian IP consultants, but also the income of the state would be lost if Indonesia joint with the Madrid System. The phenomenon above has risen some questions as to whether the system of international registration marks should be adopted by Indonesia or not. This paper tries to analyze and identify the inter national registration system based on Madrid Agreement and the Protocol, including their problems related to their implementation in Indonesia. The methodology is normative juridical of which the result of this research are the problem is not regulated whilst there are some cases reported. The result showed that ratifying international trademark registration Madrid Protocol has advantages and disadvantages for Indonesia. Based on the above discussion, basically Madrid Protocol to increase the competitiveness of the nation but need careful preparation for the run. Necessary steps to be prepared by a mature Indonesian government before joining the Madrid Protocol.Â Keywords: madrid protocol, trade mark, ratificationÂ AbstrakPenelitian ini meneliti masalah-masalah yang berkaitan dengan ratifikasi Protokol Madrid mengenai pendaftaran merek dagang Internasional. Penelitian ini akan mengkaji bagaimana dampak ratifikasi Sistem Madrid tidak hanya untuk konsultan IP Indonesia, tetapi juga pendapatan negara akan hilang jika Indonesia bergabung dengan Sistem Madrid. Fenomena di atas telah menimbulkan beberapa pertanyaan, apakah sistem tanda pendaftaran internasional harus diadopsi oleh Indonesia atau tidak. Makalah ini mencoba menganalisis dan mengidentifikasi sistem registrasi antar nasional berdasarkan Perjanjian Madrid dan Protokol, termasuk masalah mereka terkait dengan implementasinya di Indonesia. Metodologi ini adalah yuridis normatif dimana hasil penelitian ini adalah masalahnya tidak diatur sementara ada beberapa kasus yang dilaporkan. Hasil penelitian menunjukkan bahwa meratifikasi pendaftaran merek internasional Protokol Madrid memiliki kelebihan dan kekurangan untuk Indonesia. Berdasarkan pembahasan di atas, pada dasarnya Protokol Madrid untuk meningkatkan daya saing bangsa tetapi perlu persiapan yang matang untuk menjalankannya. Langkah-langkah yang perlu disiapkan oleh pemerintah Indonesia yang matang sebelum bergabung dengan Protokol Madrid.Â Kata kunci: protokol madrid, merek dagang, ratifikas